From the Difficult Airway Management to Diagnosis of Retropharyngeal Synovial Cell Carcinoma - Joanna Maria Jassem-Bobowicz; Ewa Magdalena Sokołowska; Katarzyna Monika Hinca; Izabela Drążkowska; Katarzyna Stefańska (MDPI AG, 2022)
Respiratory complications are among the most common problems addressed in neonatology in the first hours after birth, whereas the risk of any cancer in the neonatal period is 28 per million. Sarcomas, malignant mesenchymal neoplasms, account for about 8% of all neoplasms in the neonatal period. We report on a male neonate born at 36 + 4/7 weeks of gestation, diagnosed with retropharyngeal synovial carcinoma. Ineffective respiratory movements and generalized cyanosis were the first symptoms to be noted. On the ultrasound examination of the neck, a tumor of the retropharyngeal space was exposed, then visualized by an MRI of the head and neck. The biopsy analysis revealed the diagnosis of an extremely rare tumor in a neonate. The location of its growth was atypical, contributing to a diagnostic challenge. The neoplasm was treated solely with chemotherapy concordantly with the CWS protocol, individually customized for our patient. Preterm birth, as in our case, 36 + 4/7 weeks of gestation, may imply a possible need for resuscitation or support in the transition period. Aggressive high-grade tumors of the head and neck region are locally invasive and prone to metastasize. However, prognosis in infants is hard to estimate, therefore both individualized treatment and multidisciplinary care should be tailored to the needs of the patient.